Bahan Ajar Berbasis Alquran Teaching Model: Pemahaman Konsep Bangun Datar Siswa SMP - Astriana Putri; Nanang Supriadi; Rizki Wahyu Yunian Putra (Universitas Muria Kudus, 2021)
This research aims to produce mathematics teaching materials based on the ALQURUN Teaching Model (ATM). This research is a research and development (R and D) with the ADDIE development model. There are 5 stages in the ADDIE development model, namely: (1) Analysis; (2) Design; (3) Development; (4) Implementation; (5) Evaluation. The data collection instruments used were: interviews, material expert validator questionnaire, media expert validator questionnaire, student response questionnaire, and concept understanding ability tests. The results of the analysis of the material expert validation and media products of teaching materials based on ALQURUN Teaching Model fall into the feasible category of use with an average of 3.58 and 3.62 of the maximum score 4. The results of the analysis of student responses in small-scale trials (10 students) Large scale (20 students) for the developed teaching materials obtained very attractive criteria with an average score of 3.48 and 3.65 from a maximum score of 4. While the results of the effectiveness test of teaching material products developed towards improving students' understanding of mathematical concepts obtained the moderate category. with an effect size of 0.50 for SMPN in Lampung Utara. From these results,it shows that the produce mathematics teaching materials based on the ALQURUN Teaching Model (ATM) is very feasible to be used in supporting learning activities in the classroom.